Bioprocessed Wheat Ingredients: Characterization, Bioaccessibility of Phenolic Compounds, and Bioactivity During in vitro Digestion - Tomé-Sánchez, Irene; Martín-Diana, Ana Belén; Peñas, Elena; Frias, Juana; Rico, Daniel; Jiménez-Pulido, Iván; Martínez-Villaluenga, Cristina (Frontiers in Plant Science, 2021)
To enlarge the applications of whole wheat grain (WWG) and wheat bran (WB) as functional ingredients in foodstuffs that can promote human health, researchers have explored bioprocessing approaches to improve the bioaccessibility of phenolic compounds from these food matrices and, subsequently, their biological effects. The objective of this study was to compare the composition in nutrients, anti-nutrients and bioactive compounds of WWG and WB and their respective bioprocessed products: sprouted wheat (GERM) and WB hydrolysate (stabilized by spray-drying [SPD] and microencapsulated [MEC]. In addition, to evaluate the functional properties of these ingredients the bioaccessibility of phenolic compounds and their potential antioxidant and anti-inflammatory activities were monitored at different digestion steps. GERM had increased amounts of insoluble dietary fiber, a higher diversity of oligosaccharides and higher concentration of monosaccharides, free phosphorous and phenolic compounds as compared to WWG. SPD had improved content of soluble dietary fiber, oligosaccharides, monosaccharides, free phosphorous, phenolic compounds (vs. WB )whereas MEC was mainly composed by protein and nearly a 2-fold lower content of SPD components. All ingredients showed lower amounts of phytic acid as compared with raw materials. In all samples, hydroxycinnamic acids were the most representative polyphenols followed by minor amounts of hydroxybenzoic acids and flavonoids. Gastrointestinal digestion of GERM, SPD, and MEC revealed a high stability of total phenolic compounds in both gastric and intestinal phases. Hydroxycinnamic acids were the most bioaccesible compounds during digestion in the three bioprocessed wheat ingredients studied although their bioaccesibility varied across ingredients. In this sense, bioaccessibility of FA derivatives increased in GERM with the progression of digestion while it was reduced in SPD and MEC up to the end of the intestinal phase. Microencapsulation of SPD with pea protein led to generally to lower bioaccesible amounts of phenolic acids. Comparison analysis of biological effects highlighted SPD for its most potent antioxidant effects in the gastrointestinal tract (3 out 4 antioxidant parameters with highest values) while no clear differences were observed as regards to the in vitro anti-inflammatory activity. Overall, these results support the potential application of GERM, SPD and MEC as functional and nutraceutical ingredients.